MONITORING KADAR AIR TANAH MELALUI PENGUKURAN SIFAT DIELEKTRIK PADA LAHAN JAGUNG - Bandi Hermawan (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2005)
This research aims to monitor soil water content in the field through the measurement of the electrical impedance during the early period of corn growth in the dry season. Two levels of tillage and four types of mulch were arranged at a split plot design with three replications. Part of experiment plot was cultivated twice and the other part was not cultivated. Each main plot was then divided into four sub-plots of 3 x 4 m each of wich was applied with 100% imperata mulch, 80% imperata and 20% kerinyu mulch, 50% imperata and 50% kerinyu, or 100% kerinyu. Two sets of wire, where the lowest 10 cm part was not isolated, were inserted into 10 and 20 cm soil depth therefore they measured the electrical impedance at the 0-10 and 10-20 cm soil layers. The electrical impedance values were measured using the digital ohm-meter that produce the electrical current at frequency of 1 kHz. Results show that the measured electrical impedance values have a very high sensitivity to the fluctuation of soil water content in the field. When calibrated to the same soil, the values can be transformed into water content values. During the measurement period, the cultivated soil is consistently drier at the 0-10 depth and wetter at the 10-20 depth compared to the uncultivated soil. The combination of 50% imperata and 50% kerinyu mulch maintains higher soil water content uring the dry season compared to other combinations. The research suggests that monitoring of soil water content can be conducted directly in the field through the measurement of electrical impedance.